صور القرض الحكمي وأحكامه في الفقه الإسلامي - جعفر، عبدالقادر جعفر (جامعة غرداية, 2020)
القروض الحكمية ذات صور وأسباب كثيرة، وربما لم ينتبه المسلم إلى أحكامها الخاصة وآثارها المختلفة لكونها تحمل أسماء ليست صريحة في القرض. يأتي هذا البحث ليبرز صور هذا النوع من القروض، قديما وحديثا، فيبين أهم أحكامها، مجيبا، بمنهج الوصف والتحليل والاستقراء على إشكالية رئيسة هي: ما هو القرض الحكمي، وما أهم صوره وأحكامه؟ وذلك في مطالب ثلاثة؛ الأول في مبادئ القرض الحكمي، والثاني في صوره، والثالث في أحكامه. ويصل البحث إلى نتائج منها: أن القرض الحكمي: هو دفع المال لقضاء حاجة الغير بنية القرض. وقد انفرد الشافعية بهذه التسمية، وأورده غيرهم دون تمييز بينه وبين الحقيقي في التسمية، وأنه مشروع عند عامة الفقهاء، وإن اختلفوا في بعض تفاصيله، وأن للقرض الحكمي عناصر زائدة عن الحقيقي اقتضتها طبيعته، وله صور كثيرة يترتب عنها جميعها – عند تحقق شروطها – قرض في ذمة المؤدى عنه يوجب له حق الرجوع عليه بمثله أو قيمته، ويمنع عليه أي نفع للمقرض كما في القرض الحقيقي.
The ruling loans (al-qorudh al-hukmiyyah) have many types and reasons, and perhaps the Muslim did not pay attention to their own provisions and their different effects because they don't explicitly reflect the loan. This research highlights the types of loan, both conventional and contemporary, showing the most important provisions. This research has used the descriptive and the analytical method to answer the main problem, which is: what is the definition of the loan judgment, and what is its most important form and provisions? This is going to be done in three chapters; firstly the principles of the loan judgment, secondly its forms, and thirdly its provisions. The research findings show that the loan judgment (al-qardh al-hukmi) refers to paying money in order to fulfill the need of others with the intention of loan. only al-shaafa'ia refered to this type of loan with this name, while others didn't differentiate between this loan and the other loans, (al-qardh al-hukmi) is considered permissible among most jurists, although they differ in some of its details. Due to its specific nature, (al-qardh al-hukmi) has more elements than the (conventional) one. If a person performs it, he shall have the right to retraction either similar to it or with same value, and any benefit to the lender shall be prohibited as in the real loan.
Keywords: القروض البنكية -- المعاملات المالية -- الفقه الإسلامي